Antibody Seronegativity in COVID-19 RT-PCR–Positive Children. Issue 8 (13th July 2022) - Bhatt, Maala; Zemek, Roger L.; Tang, Ken; Malley, Richard; Plint, Amy C.; Pham-Huy, Anne; Dawson, Jennifer; McGahern, Candice; Pelchat, Martin; Arnold, Corey; Galipeau, Yannick; Langlois, Marc-André
Abstract : This substudy of a prospective case-ascertained household transmission study investigated severe acute respiratory syndrome coronavirus 2 reverse transcription polymerase chain reaction–positive individuals without antibody development and factors associated with nonseroconversion. Approximately 1 of 8 individuals with coronavirus disease 2019 did not seroconvert. Children, particularly the youngest, were approximately half as likely to seroconvert compared with adults. Apart from the absence of fever/chills, individual symptoms did not strongly predict nonseroconversion.